A peculiar manifestation and clinical course of occult primary hyperparathyroidism: a case report - Loderer, Tommaso; Rossini, Matteo; Cozzani, Federico; Bonati, Elena; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2021)
We present the clinical case of a patient who developed acute hypercalcemia diagnosed after presenting acute pancreatitis.Male patient, age 67, arrived at the Emergency Department of the University Hospital of Parma for upper abdominal pain, radiated to the back, and associated with nausea. Laboratory tests showed elevation of lipase, serum calcium levels, PTH levels and serum creatinine. Due to the persistence on hypercalcemia an ultrasound scan of the cervical region was performed and showed a hyperechoic nodule of about 25x26x30 mm at the level of the lower pole of the left thyroid lobe, compatible with hyperplastic parathyroid. In the light of clinical-radiological examinations, acute edematous pancreatitis due to hypercalcemia was diagnosed. Hypercalcemia was attributable to primary hyperparathyroidism, so surgical indication to parathyroidectomy was gave.After medical treatment there was a progressive improvement of the clinical conditions and a few days later the patient underwent surgical operation of lower left parathyroidectomy with progressive normalization of the serum calcium levels. If hypercalcemia persists ​​after the beginning of a specific therapy there is an indication to perform an emergency parathyroidectomy; in our case the surgical procedure was performed some days after the diagnosis because the calcium serum levels ​​had returned to normal values with significant improvement of the clinical conditions, despite persistence of high PTH values.